Microstructural, mechanical, and acoustic analyses of concrete with EPS and silica fume - Victor Gaspar Silva e Silva; Cimark Guimarães Sandes Filho; Andressa Fernanda Angelin; Antonio Ernandes Macedo Paiva; Stella Stopa Assis Palma; Raquel Gonçalves; Rosa Cristina Cecche Lintz; Luísa Andréia Gachet; Edson Jansen Pedrosa de Miranda Jr. (Revista IBRACON de Estruturas e Materiais)
Abstract The incorporation of expanded polystyrene (EPS) into concrete reduces its density, but also its mechanical properties. Therefore, the concrete with EPS is generally considered as a non-structural material. In this study, destructive and nondestructive techniques were used to analyze the microstructural, mechanical, and acoustic performances of a concrete produced by the particle packing method, replacing an increasing percentage (5 to 20%) of the coarse aggregate volume by EPS. The mechanical properties decreased, but not enough for the EPS concrete to be considered as non-structural; the microstructure showed disorder in its transition zone, and this disorder was captured by the acoustic analysis. Moreover, the sound wave attenuation increased at 10 and 20% of EPS.